2023
DOI: 10.1002/mds.29429
|View full text |Cite
|
Sign up to set email alerts
|

Reduced and Delayed Cerebrovascular Reactivity in Patients with Parkinson's Disease

Sephira G. Ryman,
Nicholas Shaff,
Andrew Dodd
et al.

Abstract: Background Cerebrovascular dysfunction in Parkinson's disease (PD) is heterogeneous and may contribute to disease pathophysiology or progression. There is a need to understand the mechanisms by which cerebrovascular dysfunction is altered in participants with PD. Objectives The objective of this study is to test the hypothesis that participants with PD exhibit a significant reduction in the ability of the cerebral vessels to dilate in response to vasoactive challenges relative to healthy controls (HC). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…In the current study, using rsfMRI, reduced CVR was observed in certain cortex in PD, compared to HCs. Our in vivo findings supported that microvascular dysfunction might be involved in pathophysiology of PD, consistent with above‐mentioned studies in vitro and a previous study using transcranial Doppler in the patients with PD 33 and another study using BOLD fMRI with hypercapnia 18 . The temporal and occipital involvements were reported in PD, especially in PD with cognitive dysfunction 34,35 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, using rsfMRI, reduced CVR was observed in certain cortex in PD, compared to HCs. Our in vivo findings supported that microvascular dysfunction might be involved in pathophysiology of PD, consistent with above‐mentioned studies in vitro and a previous study using transcranial Doppler in the patients with PD 33 and another study using BOLD fMRI with hypercapnia 18 . The temporal and occipital involvements were reported in PD, especially in PD with cognitive dysfunction 34,35 .…”
Section: Discussionsupporting
confidence: 91%
“…Although no significant differences were detected between the two groups, CVR in the corpus striatum was proved to reflect motor symptom severity. Another latest study found reduced and delayed whole brain CVR in PD patients compared with HC 18 . However, Al‐Bachari et al 19 demonstrated no statistically significant differences in CVR between PD and healthy controls (HCs).…”
mentioning
confidence: 97%